Deep Eutectic Solvents as Reaction Media for the Palladium‐Catalysed C−S Bond Formation: Scope and Mechanistic Studies. Issue 44 (18th July 2017) - Marset, Xavier; Guillena, Gabriela; Ramón, Diego J.
Abstract: A unique jigsaw catalytic system based on deep eutectic solvents and palladium nanoparticles where C−S bonds are formed from aryl boronic acids and sodium metabisulfite, is introduced. The functionalization step is compatible with a broad spectrum of reagents such as nucleophiles, electrophiles or radical scavengers. This versatile approach allows the formation of different types of products in an environmentally friendly medium by selecting the components of the reaction, which engage one with another as pieces in a jigsaw. This simple procedure avoids the use of toxic volatile organic solvents allowing the formation of complex molecules in a one‐pot reaction under mild conditions. Despite the fact that only 1 mol % of metal loading is used, the recyclability of the catalytic system is possible. Kinetic experiments were performed and the reaction order for all reagents, catalyst and ligand was determined. The obtained results were compared to palladium nanocrystals of different known shapes in order to shed some light on the properties of the catalyst. Abstract : Piecing the puzzle : A unique catalytic system, where C−S bonds are formed from aryl boronic acids and sodium metabisulfite, is introduced. The functionalization step is compatible with nucleophiles, electrophiles or radical scavengers and principles of green chemistry, as in a jigsaw. Kinetic experiments were performed, and the results were compared to palladium nanocrystals of different known shapes in order to shed some light on the properties of the catalyst.